2005
DOI: 10.1103/physrevb.72.100103
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric transition inYMnO3from first principles

Abstract: We have studied the structural phase transition of multiferroic YMnO3 from first principles. Using group-theoretical analysis and first-principles density functional calculations of the total energy and phonons, we perform a systematic study of the energy surface around the prototypic phase. We find a single instability at the zone-boundary which couples strongly to the polarization. This coupling is the mechanism that allows multiferroicity in this class of materials. Our results imply that YMnO3 is an improp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

35
378
4
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 408 publications
(419 citation statements)
references
References 24 publications
35
378
4
2
Order By: Relevance
“…Our model is based on the general expression for the free energy of the hexagonal RMnO 3 series obtained from group theoretical considerations [21][22][23] and confirmed by DFT. 22 More specifically, DFT reveals that the K 3 mode nearly displays a continuous U (1) …”
Section: Monte-carlo (Mc) Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our model is based on the general expression for the free energy of the hexagonal RMnO 3 series obtained from group theoretical considerations [21][22][23] and confirmed by DFT. 22 More specifically, DFT reveals that the K 3 mode nearly displays a continuous U (1) …”
Section: Monte-carlo (Mc) Simulationsmentioning
confidence: 99%
“…On the theoretical side, the two-transition scenario has initially been supported by density-functional-theory calculations 20 . A more detailed analysis, however, suggests improper ferroelectricity triggered by the lattice trimerization in a single-step transition 21,22 , in which secondary anomalies are yet possible due to the breaking of residual symmetries 23 . Direct measurement of the spontaneous polarization as function of temperature would clarify this puzzling situation.…”
mentioning
confidence: 99%
“…A symmetry analysis [15,24,25] shows that there are three possible paths from the high temperature P6 3 /mmc phase to the room temperature ferroelectric P6 3 cm phase, summarized in figure 1. Fennie et al [25] and Kim et al [23] supported the path of a single transition (at ∼1270 K), driven by a K 3 order parameter which couples to a secondary zone centre order parameter (associated with − 2 ) to induce ferroelectricity. In contrast to this, some studies [14,24,26] have suggested one of the paths that involves an intermediate phase between the paraelectric P6 3 /mmc phase and the ferroelectric P6 3 cm phase.…”
Section: Introductionmentioning
confidence: 99%
“…But for the improper FEs, the FE mode is no longer the primary order parameter, i.e., the polarization is induced by one or two rotational modes. [13][14][15][16][17][18][19][20][21][22][23][24][25] To verify whether the ½111 -superlattice LaCoO 3 /LaAlO 3 is an improper FE or not, the stability of the FE mode will be examined. We adopt the ISOTROPY software 33 to obtain the symmetry-adapted phonon modes in the low-symmetry FE structure.…”
Section: General Design Guidelinesmentioning
confidence: 99%
“…12 The typical example of the conventional improper FEs is hexagonal manganite YMnO 3 , 13 where the FE buckling (P mode) of the Y-O planes is induced by the non-polar MnO 5 polyhedra tilt (Q mode). 13,14 The free energy expansion in this system contains the coupling term (PQ 3 ) between the Q and P, indicating that the non-polar distortion Q must be reversed. 15 The hybrid improper ferroelectricity (HIF) was recently discovered in the artificial superlattice PbTiO 3 /SrTiO 3 , 16 where the ferroelectricity is induced by a trilinear coupling (PQ 1 Q 2 ) between the FE mode (P) and two oxygen octahedral rotational modes (Q 1 and Q 2 , respectively).…”
Section: Introductionmentioning
confidence: 99%